AUTODERMOPLASTIC IN MEDICAL TREATMENT OF PROLONGED NOT HEALING ULCERS AND WOUNDS OF LOWER EXTREMITIES AT PATIENTS WITH DIABETES MELLITUS - Gerasimov, G.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The analysis ofautodermoplasty efficiency in treatment of prolonged not healing ulcers and wounds of the lower extremities at 52 patients with diabeteses mellitus using miscellaneous local treatment facilities and preparing to operations are presented in the article.On example of three groups of patients is proved higher efficiency of autodermoplasty (98.4±1.2%) when use Prostaglandin E1, a 5% S-aminocapronic acid solution and gel of Solcoseril before the operation at this category of patients.